Stevens–Johnson Syndrome associated with mogamulizumab treatment of adult T‐cell leukemia / lymphoma. Issue 5 (10th March 2013) - Ishida, Takashi; Ito, Asahi; Sato, Fumihiko; Kusumoto, Shigeru; Iida, Shinsuke; Inagaki, Hiroshi; Morita, Akimichi; Akinaga, Shiro; Ueda, Ryuzo
<x xml:space="preserve">Abstract</x> We report an adult T‐cell leukemia/lymphoma patient suffering from Stevens–Johnson Syndrome (SJS) during mogamulizumab (humanized anti‐CCR4 monoclonal antibody) treatment. There was a durable significant reduction of the CD4+CD25highFOXP3+ regulatory T (Treg) cell subset in the patient's PBMC, and the affected inflamed skin almost completely lacked FOXP3‐positive cells. This implies an association between reduction of the Treg subset by mogamulizimab and occurrence of SJS. The present case should contribute not only to our understanding of human pathology resulting from therapeutic depletion of Treg cells, but also alert us to the possibility of immune‐related severe adverse events such as SJS when using mogamulizumab. We are currently conducting a clinical trial of mogamulizumab for CCR4‐negative solid cancers (UMIN000010050), specifically aiming to deplete Treg cells.